LOVE OF THE HOMELAND AND DEFENSE OF THE NATION IN INDONESIA: STUDYING THE ESSENCE OF THE TEACHINGS OF RELIGIOUS MODERATION IN THE QUR’AN - Basid, Abd.; Izzuddin, Ahmad; Hakim, Abdul; Husna, Rifqatul (MUSHAF: Jurnal Tafsir Berwawasan Keindonesiaan, 2024)
This research focuses on the issue of patriotism, which is then linked to the foundations of the Qur’an and Hadith, its contextualization with Indonesia (NKRI), and its relationship with the caliphate, imamate, and similar Islamic political systems. The indicators of patriotism and its contextualization with NKRI are important to discuss, given that many circles question the democratic system in Indonesia and consider it a rejected system, taghut, and a form of disbelief, such as groups like Hizb al-Tahrīr (HT), the Islamic State of Iraq and Syria (ISIS), Khilafatul Muslimin (KM) who promote the concept of the caliphate, Shia who promote the concept of the imamate, and the like. The research is motivated by the recent phenomenon of many young Indonesians being affected by the aforementioned ideologies and becoming overly zealous in their religion. This concern is supported by survey results from several institutions. A survey by the Lembaga Kajian Islam dan Perdamaian (LaKIP) on radicalism among students and Islamic Education (PAI) teachers in Jabodetabek from October 2010 to January 2011 showed that nearly 50% agreed with radical actions; 25% of students and 21% of teachers stated that Pancasila was irrelevant; 84.8% of students and 76.2% of teachers agreed with the implementation of Islamic law; and 52.3% of students and 14.2% justified bomb attacks. The Pew Research Center’s 2015 study revealed that about 10 million Indonesians supported ISIS, most of whom were young people. This research attempts to objectively view the above phenomenon based on the Qur’an and Hadith literature and its relation to the concept of dar al-mitsaq, so that the people of this country, especially its youth, do not become overly zealous in their religion. Ultimately, this research concludes that: 1) There are ten indicators of religious moderation practices, including patriotism, which is defined as the feeling that arises from the heart of a citizen to serve, maintain, defend, and protect their homeland from all threats and disturbances, willing to sacrifice for the interests of their nation and country, and love the customs and culture of their nation, thus not easily accepting offers from other nations that could harm their own nation; 2) Like the Medina Charter, Pancasila is a national consensus agreed upon by the founding fathers of Indonesia. All nations within it, without exception, are protected by the state as long as they do not violate the agreement and do not break the law in terms of norms, ethics, and legality.